Router as a Data Traffic Controller in Computer Networks - Sukma, Kemala; Ilham, Dirja Nur; Candra, Rudi Arif; Yunan, Amsar; Anwar, Ihsan (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
The rapid development of computer networks has led to an increasing demand for efficient and reliable data traffic management. Network complexity, which involves various devices and communication paths, requires systems capable of controlling data flow optimally. A router is a network device that functions as an inter-network connector and determines the best path for data packet transmission. This article aims to examine the role of routers in managing data traffic in computer networks based on a literature review. The method used is a literature study of scientific articles and reference books related to computer networks and routing technologies. The results show that routers play a vital role in improving network performance, optimizing data delivery, and maintaining network stability and security.